Criollismo and cultural diplomacy between Perón and Ibáñez (Santiago-Buenos Aires, 1953) - Casas, Matias Emiliano; Donoso Fritz, Karen (Revista de Historia Social y de las Mentalidades, 2025)
This article analyzes cultural diplomacy as manifested in the "esquinazo" performed by Chilean “huasos” for Perón in Santiago and the Argentine “malón criollo” organized in honor of Ibáñez in 1953. We consider that these demonstrations sought to strengthen discourses on Chilean-Argentinian brotherhood and the leadership of these presidents through the use of cultural stereotypes that revealed a long process of invented tradition. Drawing from internal correspondence of the groups that carried out these demonstrations, photographic and audiovisual material, official publications, and press attention, we focus on these diplomatic visits and the effects they caused.